(N+0)+(n+1)=-389

Simple and best practice solution for (N+0)+(n+1)=-389 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (N+0)+(n+1)=-389 equation:


Simplifying
(N + 0) + (n + 1) = -389

Reorder the terms:
(0 + N) + (n + 1) = -389
Remove the zero:
(N) + (n + 1) = -389
N + (n + 1) = -389

Reorder the terms:
N + (1 + n) = -389

Remove parenthesis around (1 + n)
N + 1 + n = -389

Reorder the terms:
1 + N + n = -389

Solving
1 + N + n = -389

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + N + -1 + n = -389 + -1

Reorder the terms:
1 + -1 + N + n = -389 + -1

Combine like terms: 1 + -1 = 0
0 + N + n = -389 + -1
N + n = -389 + -1

Combine like terms: -389 + -1 = -390
N + n = -390

Add '-1n' to each side of the equation.
N + n + -1n = -390 + -1n

Combine like terms: n + -1n = 0
N + 0 = -390 + -1n
N = -390 + -1n

Simplifying
N = -390 + -1n

See similar equations:

| w^2=77 | | 8.5+j=17.6 | | 7x=6x+72 | | 5/3x+1/3x=211/3+7/3x | | 392/2 | | 1/12+3/8y=5/12 | | 5x+26(x-2)=103 | | 5(5x+22)=5 | | 4x-45=x^2 | | derp= | | KLN=9x-7 | | -(3a+4a-6)+2(9a+3)+3(-8a)= | | 2(11m-10)+6m=-6(-6m+2)-8 | | 13m-5=4m | | 784/2 | | 4(2x-5y)=-13 | | 4.3(g-7)=2(10+g) | | N+(n+1)=-389 | | 0.15y+0.08(y+7000)=1480 | | 7f-2(f+8)=29 | | r^2+8r-29=0 | | 10+6X-3= | | 6.5+j=12 | | x+3=7x-35 | | c(2c+3)+c-3(7+4c)= | | 2c-15=c+4 | | 4x+x+4x+x+5=180 | | 7+3/7+1/4-5-1/14 | | 2(11m-10)+6=-6(-6m+2)-8 | | 6x+9x=14x | | 40k+80k=30k+90 | | 6t+1/6=t+4/12+t-2/12 |

Equations solver categories